Experiencing Virtual Training via e-CPD: Analysis of Creative Thinking Skills - Rafiza, A.R.; Kandan, N.; Yusop, F.D.
This research investigated the experience of virtual training via electronic Continued Professional Development (e-CPD): analyzing teachers’ creative thinking skills. The data analyzed was e-CPD content analysis related to teachers’ creative thinking skills. The research finding portrays the gradation of creative thinking skills in experiencing e-CPD. The results contribute to improving virtual training for teachers’ professional development thereby training teachers to become more efficient users of technology. Copyright@ 2014 University of Malaya all right reserved